2015
DOI: 10.1038/nrc3967
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and cancer risk: new mechanistic insights from epidemiology

Abstract: Excess body adiposity, commonly expressed as body mass index (BMI), is a risk factor for many common adult cancers. Over the past decade, epidemiological data have shown that adiposity-cancer risk associations are specific for gender, site, geographical population, histological subtype and molecular phenotype. The biological mechanisms underpinning these associations are incompletely understood but need to take account of the specificities observed in epidemiology to better inform future prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
443
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 525 publications
(461 citation statements)
references
References 166 publications
9
443
3
6
Order By: Relevance
“…There is a complex array of biological mechanisms through which obesity may influence prostate carcinogenesis and metastasis, including hyperinsulinemia, elevated insulin-like growth factor (IGF) hormone levels, dysregulation of sex steroid hormones, altered levels of adipokines, and chronic inflammation (3,44). Hyperinsulinemia has been associated with increased circulating levels of IGF-1, which have been found to promote carcinogenesis, including within the prostate (45)(46)(47).…”
Section: Articlementioning
confidence: 99%
“…There is a complex array of biological mechanisms through which obesity may influence prostate carcinogenesis and metastasis, including hyperinsulinemia, elevated insulin-like growth factor (IGF) hormone levels, dysregulation of sex steroid hormones, altered levels of adipokines, and chronic inflammation (3,44). Hyperinsulinemia has been associated with increased circulating levels of IGF-1, which have been found to promote carcinogenesis, including within the prostate (45)(46)(47).…”
Section: Articlementioning
confidence: 99%
“…In a meta-analysis including 20 studies, Renehan et al 75 reported an overall decrease in risk of 8% (95% CI: −12 to −3) for each increment of 5 kg/m 2 in BMI. While BMI is a valid parameter for general adiposity, it does not reflect the visceral fat deposit and WC, and WHR provides a better proxy of abdominal adipose tissue, which appears to be more metabolically active than peripheral adipose tissue 25,76 .…”
Section: Body Fatnessmentioning
confidence: 99%
“…In solid malignancies, the hypoxic conditions found at the core of the tumors induce adaptive pathways aimed at maintaining lipid synthesis, homeostatic pH and cell survival [6]. The resulting metabolic changes correlate with poor prognosis, poor treatment response and recurrence in diseases such as breast, liver and brain cancer [7][8][9][10]. Emerging therapeutic approaches have thus targeted lipid synthesis to counter the effects of metabolic reprogramming in cancer cells [11,12].…”
Section: Introductionmentioning
confidence: 99%